PENINGKATAN KETERAMPILAN KERJASAMA DAN PRESTASI BELAJAR MATA PELAJARAN BAHASA INDONESIA MENGGUNAKAN MODEL PEMBELAJARAN JIGSAW II DENGAN BANTUAN MEDIA POWERPOINT KELAS IV SDN 3 JENGGAWUR - Karina Putri Nugrahaini; Pamujo Pamujo (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study was motivated by the low levels of collaboration skills and academic achievement among students in the Indonesian language subject. Many students were not actively participating in group discussions and demonstrated limited ability to share their understanding during collaborative work. Individualistic behavior persisted within group settings, resulting in only a few students completing the assigned tasks while others remained passive and failed to grasp the material. Such dynamics negatively impacted overall academic performance, indicating that the learning process had not been optimized for either educators or learners. The aim of this research was to improve students collaboration skills and academic achievement in Indonesian language learning by implementing the Jigsaw II learning model with the support of the Canva digital application among Grade IV students at SDN 3 Jenggawur. The researcher sought to integrate digital tools, specifically Canva, to enhance the learning experience. This classroom action research was conducted in two cycles involving 17 students (11 boys and 6 girls). Data collection methods included observation, testing, and documentation. The findings revealed that the percentage of students achieving the targeted collaboration skills increased from 47% in Cycle I to 82% in Cycle II. Similarly, the percentage of students meeting the academic achievement target rose from 52% in Cycle I to 82% in Cycle II. In conclusion, the implementation of the Jigsaw II learning model assisted by the Canva application effectively improved both collaboration skills and academic achievement in Indonesian language learning among Grade IV students at SDN 3 Jenggawur in the 2024/2025 academic year.